Hydrogen Sulfide Attenuates Particulate Matter-Induced Emphysema and Airway Inflammation Through Nrf2-Dependent Manner - Jia, Guohua; Yu, Siwang; Sun, Wanlu; Yang, Jin; Wang, Ying; Qi, Yongfen; Chen, Yahong (Frontiers in Pharmacology, 2020)
Purpose: To investigate whether hydrogen sulfide provide protective effects on atmosphere particulate matter (PM)-induced emphysema and airway inflammation and its mechanism. Methods: Wild type C57BL/6 and Nrf2 knockout mice were exposed to PM (200𝜇g per mouse). Hydrogen sulfide or propargylglycine were administered by intraperitoneal injection respectively 30 mins before PM exposure, mice were anesthetized 29th day after administration. Mice emphysema, airway inflammation and oxidative stress were evaluated, the expression of NLRP3, active caspase-1 and active caspase-3 were detected. Alveolar epithelial A549 cells line were transfected with control siRNA or Nrf2 siRNA and then incubated with or without hydrogen sulfide for 30 mins before exposed to fine particulate matter for 24 hours, cell viability, TUNEL assay, the secretion of IL-1𝛽, ASC speck formation, the expression level of NLRP3, active caspase-1 and active caspase-3 were measured. Results: PM significantly increased mice emphysema and airway inflammation measured by mean linear intercept, alveolar destroy index and total cell, neutrophil counts, cytokines IL-6, TNF-𝛼, CXCL1, IL-1𝛽 in bronchoalveolar lavage fluid. PM-induced mice emphysema and airway inflammation was greatly attenuated by hydrogen sulfide, while propargylglycine aggravated that. PM-induced oxidative stress was reduced by hydrogen sulfide as evaluated by 8-OHdG concentrations in lung tissues. The expression of NLRP3, active caspase-1 and active caspase-3 enhanced by PM were also downregulated by hydrogen sulfide in mice lung. The protective effect of hydrogen sulfide on emphysema, airway inflammation, inhibiting oxidative stress, NLRP3 inflammasome formation and anti-apoptosis was inhibited by Nrf2 knockout in mice. Similarly, hydrogen sulfide attenuated the secretion of IL-1𝛽, NLRP3 expression, caspase-1 activation, ASC speck formation and apoptosis caused by fine particulate matter exposure in A549 cells but not in Nrf2 silenced cells. Conclusion: Hydrogen sulfide played a protect role in PM-induced mice emphysema and airway inflammation by inhibiting NLRP3 inflammasome formation and apoptosis via Nrf2-denpendent pathway.